Screening Consolidated Clinical Document Architecture (CCDA) Documents for Sensitive Data Using a Rule-Based Decision Support System - Rocha, Beatriz H; Pabbathi, Deepika; Schaeffer, Molly; Goldberg, Howard S (Applied Clinical Informatics, 2017)
Background: The Centers for Medicare & Medicaid Services’ Stage 2 final rule requires that eligible hospitals provide a visit summary electronically at transitions of care in order to qualify for “meaningful use” incentive payments. However, Massachusetts state law and Federal law prohibit the transmission of documents containing “sensitive” data unless there is a new patient consent for each transmission.Objectives: To describe the implementation and evaluation of a rule-based decision support system used to screen transition of care documents for sensitive data.Methods: We implemented a rule-based document screening system to identify transition of care documents that might contain sensitive data. The transmission of detected documents is withheld until a new patient consent is obtained. The documents that were flagged as containing sensitive data were reviewed in two different time periods to verify that the decision support system was not missing documents or withholding more documents than necessary.Results: The rule-based screening system has been in regular production use for the past 18 months. During the first evaluation period, 3% of 5,841 documents were identified as containing sensitive data (true-positive rate of 44%). After additional enhancements to the rules, the system was evaluated a second time and 4.5% of 6,935 documents were identified as containing sensitive data (true-positive rate of 98.4%).Conclusion: The analysis of the system demonstrates that production rules can be used to automatically screen the content of transition of care documents for sensitive data. The utilization of the rule-based decision support system enabled our hospitals to achieve meaningful use and, at the same time, remain compliant with state and federal laws.
Keywords: Clinical decision support; meaningful use; health information exchange; continuity of patient care